ANALYSIS OF HOUSEHOLD LEXICAL UNITS IN ENGLISH AND UZBEK LANGUAGES - Jamila RUSTAMOVA (Scholar Express Journal, 2023)
The article titled "Analysis of Household Lexical Units in English and Uzbek Languages" aims to compare and contrast the lexical units used in the English and Uzbek languages when referring to household items, objects and activities. The study is conducted through a corpus-based analysis of relevant literature, dictionaries, and other sources. The article starts with a brief introduction to the importance of studying lexical units and their role in language acquisition, communication, and culture. Then, it presents a theoretical framework for the analysis of lexical units, including concepts such as semantic fields, collocations, and connotations. The main part of the article focuses on the comparison of the household lexical units in English and Uzbek. The lexical units are categorized into semantic fields such as furniture, kitchenware, cleaning tools, etc. For each semantic field, the article presents a list of lexical units in both languages and analyzes their similarities and differences in terms of form, meaning, and usage
Keywords: Lexical units; english language; uzbek language; household